IMPLEMENTASI WORK FROM HOME DAN DAMPAKNYA TERHADAP KINERJA KARYAWAN - Herliana, Grace; Herdiansyah, Getrudis Anyanovena Krawing; Adriana, Erica (Journal of Business And Entrepreneurship, 2023)
Working from home as a response to the global pandemic has brought significant chances to the world of work. This research aims to examine the implementation of remote work and its impact on employee performance. The study demonstrates that employee performance is significantly influenced by the implementation of remote work. One of the benefits found is the flexibility of time provided by working from home, allowing employees to adjust their work schedules to their personal needs. Additionally, there is a positive correlation between employee productivity and a more comfortable work environment with fewer distractions. However, the research also indentifies several challenges faced by workers when working from home. Feelingsof social isolation, a lack of team collaboration, and difficulties in communication are some of these challenges. Organizations need to provide adequate technologiical infrastructure and apporopriate training to ensure that employees can easily adapt to working from home when addressing these issuies. Therefore, the implementation of remote work has a significant impact on employee performance. Benefits such as flexible working hours and increased pproductivity can be achieved, although there are some challenges that need to be addessed. Hance, it is crucial for companies to continuously monitoor and impprove remote work practices to optimiize employee performance in an ever-changing work environment.